Ship hydrostatics and stability - Biran, Adrian; López-Pulido, Rubén (Butterworth-Heinemann, 2014)
This book is a complete guide to understanding ship hydrostatics in ship design and ship performance, from first principles through basic and applied theory to contemporary mathematical techniques for hydrostatic modeling and analysis. Real-life examples of the practical application of hydrostatics are used to explain the theory and calculations using MATLAB and Excel